Phonological Awareness and Rapid Automatized Naming Are Independent Phonological Competencies With Specific Impacts on Word Reading and Spelling: An Intervention Study - Vander Stappen, Caroline; Reybroeck, Marie Van (Frontiers in Psychology, 2018)
Phonological awareness (PA) and rapid automatized naming (RAN) have been shown to be powerful predictors of reading achievement across many languages. However, literature remains unclear: (a) whether RAN is independent of PA, (b) about the specific influences of PA and RAN on reading and spelling, (c) about the efficacy of a RAN intervention. This study aims to address these issues by means of an intervention design. Precisely, the objectives are (a) to determine whether training one competence involves or not an effect on the other, (b) to examine whether each intervention based on oral abilities (PA vs RAN), could improve word reading and word spelling performances, (c) to assess the efficacy of a RAN-objects intervention. Thirty-six French-speaking second graders, from two Belgian elementary schools, were divided into two groups, and received either a PA or a RAN-objects intervention. Twenty-five-minute lessons took place at school twice a week over a period of two months. Both groups were compared on multiple experimental measures (PA, RAN, word reading, and word spelling), before and immediately after the intervention, and six months later. Results showed specific efficacy of the two interventions, with participants trained in one ability outperforming those from the other group on this specific ability at post-test. Moreover, the PA intervention revealed transfer effects on the sub-lexical processes of spelling, while the RAN intervention enhanced word reading speed. Finally, the results demonstrated the efficacy of a RAN-objects intervention for the first time. These findings provide a new piece of evidence showing the independence of PA and RAN, each process influencing the acquisition of literacy skills in a different way. The efficacy and the specific transfer effects of both interventions open up new perspectives for prevention and targeted remediation of reading disabilities.